Federation Projects in Central Europe, 1848–1918. Issue 1 (2nd January 2016) - Lakatos, Artur Lorand
Summary: This paper deals with the less researched issue of regional federation projects in East-Central Europe from the period 1848 to 1918. Based on exhaustive research, primarily using original sources—works of the intellectuals who designed these projects—the paper examines the reasons why these federation projects were written, their historical-political context, and why these plans had to fail at their time. Similarities and differences of ideas in these projects are also presented. The intention is not to give a simple presentation of a series of historical facts, but to present some early ideas focused on regional integration, which, in turn, could also provide inspiration in the present.